Peningkatan Pemahaman Konsep Pengukuran Satuan Waktu Melalui Model Pembelajaran Tipe STAD - Insan Susilawati; Astri Sutisnawati; Luthfi Hamdani Maula (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The STAD learning model is a learning model to encourage students to encourage and help each other, to master the skills taught by the teacher. The purpose of this research is to enhance comprehension of mathematical concepts in the domain of time unit measurement achieved through the implementation of a cooperative learning model known as the STAD method. The research’s type is CAR (Classroom Action Research) that has two cycles. Each cycle has four stages; planning, implementing, observing and reflecting. The subjects of this study were 2nd graders from SDN CISARUA for the 2022/2023 academic year. In total, there were 34 students, 14 male and 20 female. The data collection was observation, test and documentation. The results showed an increase in student learning completeness from Cycle I to Cycle II. The average score of all students in Cycle I was 67.94%, which increased to 78.53% in Cycle II. In Cycle I, 58.82% of students achieved the minimum passing grade (KKM), which increased to 82.35% in Cycle II. The percentage of students who achieved the KKM increased by 23.53% from Cycle I to Cycle II. Hence, the criteria for achieving classical student learning completeness have been fulfilled.